In dubio pro lector. Ambigüedad narrativa y duda razonable en el relato “En un bosque” de Ryunosuke Akutagawa (Tema Central) - Valencia Assogna, Leonardo Pedro (2020)
Among others, there are two narrative resources for the rhetorical construction of narrative ambiguity; the “unreliable narrator” and the “fictive reader”. This article studies the combined specificity of the two procedures in the story “In a Bamboo Grove” (1921) by the Japanese writer Ryunosuke Akutagawa to make an aesthetic approach to the figure of in dubio pro reo and understand that in the hermeneutics of the judge there is a process of reading and interpretation, different from the literary one, but that can be illuminated comparatively to reflect on the imperfect evidence of the testimonies in the courts and the literary ambiguity of the narrative testimonies, their respective natures and conditionings.